Greek Cosmology and Western Historiocracy: Tracing Aristotelian Notions in the Work of K. Papaioannou - Psomakis, Ioannis (Conatus - Journal of Philosophy, 2018)
Kostas Papaioannou’s dialogue with ancient Greek thought is a key element in the work of this modern Greek thinker. In particular, the ancient Greek cosmological conception as opposed to the newer Western historical-democratic model is firmly established by the modern Greek philosopher on the Aristotelian discourse. "Conversing" with Aristotle, Papaioannou seeks to reconciliate the main features of the ancient Greek cosmos with the ones that were "constructed" during the Renaissance. The purpose of this article is to investigate the Aristotelian precepts that substantiate the distinction between the Greek way of conceiving the world and the cosmopolitanism that characterizes modern approaches.